Analisis Determinan Angka Harapan Hidup di Provinsi Jambi - Riski Amanda; Hardiani; Jaya Kusuma Edy (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze development of Life Expectancy, Poverty Level, Education Level, and GRDP per capita Life Expectancy in Jambi Province during period 2010-2024 and The Influence of Poverty Level, Education Level, and GRDP per capita on Life Expectancy in Jambi Province from 2010-2024. The method used in this study is a descriptive and quantitative method in the form of secondary data sourced from the Central Statistics Agency of Jambi Province from 2010-2024 with a Panel Data Regression analysis tool processed using Eviews 12. The results of this study with panel data regression analysis with the best model selected is the Fixed Effect Model (FEM) shows that the variables Poverty Level, Education Level and Gross Regional Domestic Product (GRDP per capita) have a significant influence on Life Expectancy in Jambi Province.